Legal framework of health promotion in Brazil - Aith, Fernando Mussa Abujamra (Revista de Medicina, 2013)
Introduction and objectives: health was recognized as a social human right by the Brazilian Constitution (Articles 6 and 196) and by international normative instruments. To fulfill the right to health, health promotion occupies a prominent role. This article aims to identify the international and national legal frameworks that currently govern the action of the Brazilian State in the field of health promotion, as well as define the rights and duties of citizens in relation to health promotion. Methods: The methodology was to research rules about health promotionedited by international and national normative organisms. Results: We identified international legal documents that make explicit reference to health promotion as well as national laws and regulations that have specific provisions on the subject. National laws and regulations have been listed following the hierarchical importance in the legal field, starting with the 1988 Constitution, going through laws and finally identifying infralegal standards (eg, resolutions). Discussion and conclusions: The normative consolidation of National Policy on Health Promotion represents a breakthrough in the institutional development of the Brazilian state. However, the issue of formal legal rules is not sufficient condition for its fulfillment. The practical consequences of these legal frameworks must be achieved by providing actions and public health promotion services across the country. The accountabilityon the implementation of legal frameworks is essential for the development of Brazil in the area of health promotion.